THE IMPACT OF PROFITABILITY AND LEVERAGE ON TAX AGGRESSIVENESS WITH INCOME SMOOTHING AS THE MEDIATOR - Alfandia, Nurlita Sukma (Berkala Akuntansi dan Keuangan Indonesia, 2024)
Information asymmetry and differences in interests between agents and principals are unavoidable problems in agency relationships. Agents with better information than other parties try to maximize their benefits by managing or manipulating reported accounting numbers. Profitability and leverage are common considerations for companies in carrying out income smoothing so that profits are stable and the company looks in good condition in the eyes of stakeholders. In addition, it is also related to the size of the corporate tax burden, so both can be factors that influence the level of corporate tax aggressiveness. This study aims to analyze the direct and indirect effects of profitability and leverage on tax aggressiveness and test the mediation of income smoothing on the effect of profitability and leverage on tax aggressiveness. The research sample was determined using a purposive sampling technique of 26 consumer non-cyclical sector companies listed on the Indonesia Stock Exchange in 2018-2020. Data were analyzed using the WarpPLS 7.0 analysis tool. The results of this study show that profitability and leverage affect tax aggressiveness. However, income smoothing does not affect tax aggressiveness. Income smoothing could not mediate the effect of profitability and leverage on tax aggressiveness. There is no indirect effect between profitability and leverage on tax aggressiveness.